An Integrated BIM System to Track the Time and Cost of Construction Projects: A Case Study. (16th November 2015) - Jrade, Ahmad; Lessard, Julien
Abstract : Many construction projects suffer from poor design and from inconsistent time and cost management. This situation has led to rethinking of the industry's performance and how it could be improved. Technology is breaking through design and management practices. Earned value management (EVM) enables better management of time and cost constraints. Building Information Modeling (BIM) is recognized to improve the planning and realization of a construction project. The present paper proposes an integrated time and cost management system (ITCMS), where an EVM platform is used in a virtual environment during the planning and construction phases of a project. The ITCMS enables early involvement and project integration plus thorough time and cost management. The system consists of four modules and 13 different processes. The ITCMS is beneficial at the design stage; construction professionals are able to synchronize the building model with time and cost parameters as well as optimize it through a clash detection process that results in budget and schedule compressions early on. The ITCMS is a useful tool for construction and engineering managers that strive to increase projects' performance. The authors demonstrate in this paper the validity of using the ITCMS through an actual project.